Habit of tooth brushing with the dental caries incidence - Retnaningsih, Dwi; Arinti, Rani (International Journal of Research in Medical Sciences, 2018)
Background: Teeth and mouth are important parts that must be kept clean, because through these organs various germs can enter. In general, dental and oral hygiene was very important for the health and well-being of the human body because it can affect the function of mastication, speech and confidence.1 Dental caries was an infectious disease that damages tooth structure and can cause cavities. Children age under 12 years old who suffer from dental and oral diseases can be affect with student achievement in school. A preliminary study conducted at SDN 2 Ngabean was 7 out of 10 children with dental caries marked with cavities, accumulating plaque and black teeth. Methods: Quantitative research with Cross Sectional study design. The population in this study were all students of grade 4 and 5 SD Negeri 2 Ngabean Boja District Kendal District in the academic at June 2017 amounted to 80 students. Statistical test using Chi Square. Iinstrument used in this study was a questionnaire of 14 questions submitted to respondents using Likert scale type. The statistical test used was chi square nonparametric correlation because independent and dependent variables use ordinal and nominal scale. Results: Results of research obtained from 80 respondents in school-age children in SD Negeri 2 Ngabean showed that of respondents students who experience dental caries as many as 48 students (60.0%), while students who did not experience dental caries as many as 32 students (40.0%). Based on the result of chi square test it can be seen that p value = 0.000 (p value <α) or 0.000 <0.05 then Ho was rejected, and Ha accepted. Conclusions: There was a correlation of tooth brushing habit with the dental caries incidence of school age children at the elementary school state Ngabean 2 Boja District, Kendal Regency.